Pengelompokkan Provinsi di Indonesia Berdasarkan Indikator Kesehatan Tahun 2023 Menggunakan Analisis Cluster - Rahmawati, Nadia Alma; Salsabila , Amanda Shofiyah; Wulandari , Sri Pingit (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Health is a fundamental human right and a key indicator of well-being that must be accessible to all citizens, in line with Indonesia's national vision of achieving a high standard of health. This study aims to classify provinces in Indonesia based on health indicators in 2023 using cluster analysis to understand the similarities and differences among provinces. The methodology includes both hierarchical and non-hierarchical cluster analysis. Hierarchical methods employ a step-by-step approach to forming clusters, with results visualized in a dendrogram to determine the optimal number of clusters. Non-hierarchical methods, such as K-Means, predefine the number of clusters and iteratively partition the data until an optimal solution is achieved. The indicators used in this study include the percentage of children under five receiving complete immunizations, married couples of childbearing age, outpatient health complaints, self-medication practices, individuals reporting health complaints, and unmet service needs. The findings reveal that the data meet the assumptions for cluster analysis. Using the complete linkage method, five optimal clusters were identified in both hierarchical and non-hierarchical analyses. This indicates that Indonesia's provinces can be grouped into five clusters based on the 2023 health indicators. The percentage of married couples of childbearing age showed the widest distribution, while unmet service needs had the lowest. This study is expected to assist the government in designing more efficient and equitable health programs.